2009
DOI: 10.1007/s00125-009-1486-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of inflammation with worsening HOMA-insulin resistance

Abstract: Aims/hypothesis We examined the cross-sectional and longitudinal relationships between C-reactive protein (CRP), a marker of low-grade inflammation, and insulin resistance and whether the association was independent of obesity and oxidative stress. Methods CRP and insulin resistance (homeostasis model assessment of insulin resistance [HOMA-IR]) data were obtained in a population-based, prospective observational study, Coronary Artery Risk Development in Young Adults (CARDIA), during 1992–2006. Results CRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 16 publications
0
55
1
1
Order By: Relevance
“…Xu et al 34 found that CRP suppressed insulin signaling in endothelial cells. The studies by Park et al 7 and Xu et al 34 appear to support the hypothesis that inflammation and endothelial dysfunction introduce IR. Additional results indicate that IR may in turn exacerbate inflammation by increasing cytokine and adipochemokine expression (including TNF-a, interleukin-6, leptin and others), elevating free fatty acid levels, and impairing endothelial nitric oxide synthase activity.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Xu et al 34 found that CRP suppressed insulin signaling in endothelial cells. The studies by Park et al 7 and Xu et al 34 appear to support the hypothesis that inflammation and endothelial dysfunction introduce IR. Additional results indicate that IR may in turn exacerbate inflammation by increasing cytokine and adipochemokine expression (including TNF-a, interleukin-6, leptin and others), elevating free fatty acid levels, and impairing endothelial nitric oxide synthase activity.…”
Section: Discussionmentioning
confidence: 74%
“…Ingelsson et al 33 found that vascular cell adhesion molecule-1, E-selectin and CRP were independently associated with metabolic syndrome (MetS) and increased HOMA-IR. Park et al 7 examined the cross-sectional and longitudinal relationships between CRP and IR and found a significant positive association between CRP and IR, in both cross-sectional and longitudinal results, even after adjusting for adiposity measurements and oxidative stress markers. Xu et al 34 found that CRP suppressed insulin signaling in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three previous studies to which our observations may be compared; they assessed changes in glycaemia or HOMA-IR as a surrogate measure of insulin resistance. The first study is the population-based Coronary Artery Risk Development on Young Adults (CARDIA) study, in which hsCRP levels in year 7 of the study were positively associated with HOMA-IR at years 15 and 20 after adjustment for age, sex, race, lifestyle factors, education and the respective baseline HOMA-IR; a similar association was found for hsCRP levels at year 15 and HOMA-IR at year 20 [17]. The mean age of the study population was 32 years at year 7 and 40 years at year 15.…”
Section: Associations Between Immunological Variables and Deterioratimentioning
confidence: 91%
“…Only a few prospective studies have tested the hypothesis that circulating levels of immune mediators can predict the deterioration of glycaemic control before the manifestation of type 2 diabetes [15][16][17]. In two studies, deterioration of glycaemia was assessed as the incidence of IFG or IGT [15,16]; another study used increases in HOMA-IR as the outcome [17].…”
Section: Introductionmentioning
confidence: 99%